The role of GenAI in transforming educational process in HEIs - Bistra Vassileva; Teodora Daneva (Business & Management Compass)
Higher education plays a critical role in shaping competent citizens and professionals globally. The emergence of generative AI (GenAI) has introduced both opportunities and challenges to traditional educational models. In response to these challenges, this paper explores the interaction of AI and educational technology (EdTech), clarifying the potential and the challenges associated with integrating AI within the educational process. The study starts with an overview of GenAI, followed by a discussion on the application of GenAI in HEIs. The study is based on a bibliometric analysis of terms related to “artificial intelligence” and “educational technology”, employing a conceptual framework derived from a systematic literature review. Findings suggest that higher education must adapt to prepare students for a GenAI-driven society, emphasising AI literacy, interdisciplinary and transformative learning, and intelligent tutoring systems.